Analisis Laba Bersih dan Manajemen Laba Model Jones Dimodifikasi Untuk Keputusan Investasi Pada Sektor Agrikultur Di BEI Setelah Implementasi Full IFRS - Tis Atin; Pujiono (Politeknik Ganesha Medan, 2022)
Many factors underlie the decision to invest an investor, which include net income and earnings management. The implementation of IFRS aims to create high quality domestic accounting standards in line with international accounting standards. This research can test whether net income and management in accordance with earnings in the agricultural sector on the IDX have an effect on stock prices after the implementation of IFRS in Indonesia. This research uses a quantitative approach to data collection by purposive sampling. The financial report data used in this study was obtained through the annual financial report (Annual Report), ICMD (Indonesian Capital Market Directory) agricultural companies listed on the IDX in 2015–2020. Stock price data uploaded on the Yahoo! Finance. This study uses multiple linear regression analysis. The results show that net income affects stock prices and can be used by investors in fundamental analysis to obtain relevant information, while earnings management has no effect on stock prices. This shows that the financial statements are useful for investors.